Causal relationship between allergy and seborrheic dermatitis - A. A. Barilo; S. V. Smirnova (Бюллетень сибирской медицины)
Seborrheic dermatitis is a chronic relapsing inflammatory skin disease associated with overproduction of sebum and activation of the fungal skin microbiota characterized by the presence of erythematous pruritic patches and plaques with greasy scales in areas rich in sebaceous glands.Aim. To study the spectrum of sensitization to food, pollen, and indoor and fungal allergens in patients with seborrheic dermatitis.Materials and methods. The study researched features of the spectrum of sensitization to food, pollen, and fungal and indoor allergens in patients with seborrheic dermatitis (n = 40, aged 15–59 years) based on the data of an objective examination and the results of an allergen-specific test, including skin prick testing.Results. It was determined that the most significant food allergens in seborrheic dermatitis are chicken eggs and grains. The incidence of polyvalent sensitization to food allergens was 40.0%. Additionally, high incidence of sensitization to pollen allergens, most often to weed and poaceae pollen, was revealed in patients with seborrheic dermatitis. Among indoor allergens, the highest incidence of sensitization was determined to house dust and Dermatophagoides pteronyssinus. Among fungal allergens, the highest incidence of sensitization was detected to Candida albicans. Conclusion. It was found that patients with seborrheic dermatitis are often sensitized to food, pollen, and indoor and fungal allergens. Therefore, allergy can be considered a risk factor for the development of pathology.